A Case Study of the Vietnamese in Toronto: Contesting Representations of the Vietnamese in Canadian Social Work Literature - Ngo, Anh (Refuge: Canada's Journal on Refugees, 2016)
This article argues that the lived experiences and challenges of the Vietnamese community in Toronto are not reflected in the social work literature that continues to represent them as exceptional refugees. Over forty years after the fall of Saigon, a qualitative research study, “Discrimination in the Vietnamese Community, Toronto,” reveals that the Vietnamese community continues to experience intergroup conflicts stemming from war- and displacement-mediated identities of region, class, and temporal periods of migration. A critical review of the social work literature, using the theoretical lens of critical multiculturalism, traces the construction of the Vietnamese Canadians as successful “boat people” as part of the larger narrative of multiculturalism. This discourse of exceptionalism allows the needs of those who fall outside the constructed identity to remain unseen and underserved. Participant responses from this small pilot study will inform future investigation into the impact of intergroup conflicts hidden under the veneer of successful integration and adaptation of refugee and migrant groups.